Maqashid sharia and Micro-Business Governance: Evidence from Guna Jaya Store Trenggalek - Agus Nur Rohman Fajarudin; Binti Masruroh (Niqosiya: Journal of Economics and Business Research, 2026)
Introduction: Micro-enterprises play an important role in supporting rural economic activities and community resilience. This study analyzes the governance and buying–selling practices of Guna Jaya Store in Gondang Village, Tugu District, Trenggalek Regency, using the maqashid sharia framework within Islamic economic law. Research Methods: The research applies a qualitative socio-legal approach, with data collected through observation, semi-structured interviews, and documentation. Data were analyzed using an interactive qualitative model combined with normative Islamic legal assessment. Results: The findings show that the store implements a trust-based family management system characterized by transparent pricing, clear transactions, and informal credit practices without additional charges. These practices reflect compliance with the principles of justice, avoidance of gharar, and prohibition of riba. From the maqashid sharia perspective, the business contributes to the protection of wealth and religious values, although its administrative governance remains simple and lacks standardized documentation. Conclusion: This study contributes to the discourse on Islamic micro-business governance by demonstrating that substantive sharia principles can be implemented in rural enterprises without formal sharia labeling, while highlighting the importance of strengthening structured management systems for long-term sustainability.